Próba konstrukcji modelu ekonometrycznego dla określenia prognozy plonów podstawowych zbóż - Zeliaś, Aleksander (Wydział Prawa i Administracji UAM, 1969)
The article contains the considerations concerning the use of an econometrical model for the determination of the prognosis of two basic crops: wheat and rye. At the base of the constructed function of production there was estimated the influence of mineral fertilization, of the progress of agricultural technology and organization and the phenomenon of transformation of the crops on harvesting. The results of the examinations formed also the base of forming the prognosis in the scope of crops of the examined agricultural products for the years 1967 -1970.
Construction of an Econometrical Prognosis Model for Basic Crops